Factors Influencing Cochlear Patency after Translabyrinthine Surgery. (August 2017) - Rodgers, Brian; Stucken, Emily; Metrailer, Aaron; Sargent, Eric
Objective: To determine predictive factors for cochlear obliteration after translabyrinthine surgery for vestibular schwannoma. Study Design: Case series with chart review. Setting: Neurotology referral center. Subjects and Methods: In total, 345 charts were reviewed, resulting in 103 patients who underwent translabyrinthine surgery between January 2010 and July 2015 and had postoperative magnetic resonance imaging (MRI) for review. Surveillance MRI performed after translabyrinthine resection of vestibular schwannomas was reviewed. Heavily T2-weighted MRI obtained an average of 21.8 months after surgery was reviewed to assess cochlear patency. Tumor size, preoperative audiograms, and MRI cochlear fluid-attenuated inversion recovery (FLAIR) intensity were compared between patients with retained cochlear patency and those without. Results: Fifty-four percent of patients retained cochlear patency after translabyrinthine surgery. Tumor size did not differ statistically between the 2 groups. There was no statistically significant difference in speech reception thresholds, pure-tone average, or word recognition scores between patent and nonpatent groups. Preoperative MRI FLAIR intensity did not differ between groups. Conclusions: More than half of patients retain cochlear patency after translabyrinthine vestibular schwannoma surgery. Cochlear patency is required for cochlear implant in patients with unilateral deafness. Preoperative tumor size, hearing performance, and intensity on MRI FLAIR do not predict cochlear patency. To prevent loss of opportunity for cochlear implantation, simultaneous implantation and cochlear lumen keeper placement are options.